(untitled) (Research, Society and Development, 2020)
The objective of this article was to evaluate the prevalence of enamel development defects (EDD) in children attended in the discipline of Children’s Clinic II of the Dentistry course of the Universidade Federal de Campina Grande (UFCG), in Patos, Paraíba, Brazil. This study was cross-sectional, observational and retrospective using clinical records, from which information was learned about the type of EDD, number of teeth affected, clinical complaint and demographic variables. The data obtained were analyzed with of IBM SPSS Statistics software, worked by descriptive statistics and submitted to fisher’s Chi-square and Exact statistical test considered significant at the level of 5% (p<0.05). 273 medical records were evaluated, of these 36 reported some enamel defect in patients, with an average of 3.16 teeth affected per child. Defects were present in children aged 3-12 years with a mean of 8.28 years (± 2.35), mostly female (61.1%) and resident of the city of Patos, Paraíba (88.9%). Its main complaints were, mainly, toothache (36.1%) and the search for treatment (25%). Defects found were incisor-molar hypomineralization (IMH), isolated hypomineralizations, hypoplasia and dental fluorosis. The present study points to a prevalence of EDD of 13.1%, and a higher frequency of hypoplasia (55.6%) and dental fluorosis (30.6%).